The Use of Fibroin-Based Biopolymers in the Medical Field and the Analysis of Fibroin Content in Silk Fiber Based on Chromato-Mass Spectrometry - Karimov A; Sodiqova M.A; Shomurotov Sh.A; Kholmuminov A.A (Genius Publishing Group, 2022)
Fibroin was isolated from cocoons and chemical analysis was performed were analyzed by gas liquid chromatography and chromatography-mass spectrometry (GCMS) to identify bioactive compounds in methanol, ethanol and acetone solution extracts. The composition and amount of amino acids in fibroin was studied. The presence of a number of biologically and chemically active substances in fibroin was checked and the validity of their use for the treatment of various wounds and silk fabrics and fibroin films for various diseases was determined
Keywords: Silkworm; Fibroin; gas liquid chromatography; chromato-mass spectrometry